Social norms and webcam use in online meetings - Zabel, Sarah; Vinan Navas, Genesis Thais; Otto, Siegmar (Frontiers in Psychology, 2022)
Face-to-face meetings are often preferred over other forms of communication because meeting in person provides the “richest” way to communicate. Face-to-face meetings are so rich because many ways of communicating (spoken language, nonverbal cues) are available to support mutual understanding. With the progress of digitization and driven by the need to reduce personal contact during the global pandemic, many face-to-face work meetings have been shifted to videoconferences. With webcams turned on, video calls come closest to the richness of face-to-face meetings. However, webcam use often remains voluntary, and some participants choose not to turn their cameras on. In order to find ways to support webcam use—when desired—we analyzed how social norms in groups affect the decision to activate a webcam in a specific meeting. Based on an online survey with N = 333 participants, we found that social norms are related to an individual’s decision to turn on the webcam, even when controlling for group size. If the number of participants with activated webcams in a university meeting increased by 25%, it was 5.92 times more likely that an individual decided to turn their webcam on, too.. Furthermore, 81.84% of respondents indicated they would turn on their webcam if participants in a meeting were explicitly asked to do so. The results demonstrate a strong relation between social norms and the decision to activate a webcam in online meetings. They build a basis for enhancing webcam use and enable a greater richness of communication in online meetings.